Influence of Si addition on structure and properties of TiB2-Si nanocomposite coatings deposited by high-power impulse magnetron sputtering. Issue 5 (1st April 2019) - Ding, Ji Cheng; Lee, Damin; Mei, Haijuan; Zhang, Teng Fei; Kang, Myung Chang; Wang, Qi Min; Kim, Kwang Ho
Abstract: TiB2 coatings with various Si doping levels were fabricated using magnetron sputtering from TiB2 and Si targets. The chemical and phase composition, microstructure, mechanical properties, and high-temperature oxidation resistance of the coatings were investigated using different techniques, such as electron probe microanalysis (EPMA), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), nanoindentation, and thermogravimetric analysis. The results revealed that the microstructure of the TiB2 coating with and without Si doping changed from an apparent columnar structure to a densely stacked structure, and finally to a nearly featureless planar structure. A certain amount of added Si limits the growth of TiB2 grains and favors the formation of a nanocomposite structure with nanocrystalline TiB2 grains embedded in an amorphous Si phase matrix, as shown by XPS and TEM results. The hardness reached a maximum value of 35.2 GPa at 4.5 at% Si and then linearly decreased upon further increasing the Si content, owing to the excessively amorphous phase in coatings. However, it is worth noting that the high-temperature oxidation resistance of the coatings was improved by Si addition, due to their compact homogeneous structure that hinders the diffusion of oxygen. The results indicate that the hardness and oxidation resistance of the coatings can be simultaneously improved by the addition of an appropriate Si content.